Environmental education at schoool: geography as an interdisciplinary practice tool - Beling, Helena Maria; Cancelier, Janete Webler; Vestena, Michele Hennig; De Campos, josiane Oliveira (Revista Ensino de Geografia (Recife), 2020)
This paper aims to present discussions referred to the environmental education importance at elementary schools, seeking to understand the legal parameters in which environmental education is supported, the importance of interdisciplinary practice and the relationship between environmental education and Geography teaching. To demonstrate how the environmental theme can be worked with Geography, practical workshops developed with students from the Dom Érico Ferrari State Elementary School, located in Nova Palma/RS, are presented. The research was made from a qualitative approach and the instruments utilized to obtain the data are bibliographic, documentary and field research. Environmental education is evidenced in laws, programs and education norms, and in educational institutions, it should be present in an articulated manner at all levels and modalities of the educational process. It was verified that the environmental education is consolidated at schools as a practice through articulated work, made with different areas of knowledge, taking as reference the reality and the relationships established at a local level and its interface with global dynamics.